Combinatorial algorithms : 25th International Workshop, IWOCA 2014, Duluth, MN, USA, October 15-17, 2014, Revised selected papers /: 25th International Workshop, IWOCA 2014, Duluth, MN, USA, October 15-17, 2014, Revised selected papers. (2015) - Unknown
No abstract available